Effects of anterior compartment fasciotomy on intramuscular compartment pressure in patients with chronic exertional compartment syndrome. Issue 5 (24th April 2018) - Roscoe, David; Roberts, A J; Hulse, D; Shaheen, A F; Hughes, M P; Bennet, A N
Abstract : Background: Patients with chronic exertional compartment syndrome (CECS) have pain during exercise that usually subsides at rest. Diagnosis is usually confirmed by measurement of intramuscular compartment pressure (IMCP) following exclusion of other possible causes. Management usually requires fasciotomy but reported outcomes vary widely. There is little evidence of the effectiveness of fasciotomy on IMCP. Testing is rarely repeated postoperatively and reported follow-up is poor. Improved diagnostic criteria based on preselection and IMCP levels during dynamic exercise testing have recently been reported. Objectives: (1) To compare IMCP in three groups, one with classical symptoms and no treatment and the other with symptoms of CECS who have been treated with fasciotomy and an asymptomatic control group. (2) Establish if differences in IMCP in these groups as a result of fasciotomy relate to functional and symptomatic improvement. Methods: Twenty subjects with symptoms of CECS of the anterior compartment, 20 asymptomatic controls and 20 patients who had undergone fasciotomy for CECS were compared. All other possible diagnoses were excluded using rigorous inclusion criteria and MRI. Dynamic IMCP was measured using an electronic catheter wire before, during and after participants exercised on a treadmill during a standardised 15 min exercise challenge. Statistical analysis included t-tests and analysis of variance. Results: Fasciotomy results in reduced IMCP at all time points during a standardised exercise protocol compared with preoperative cases. In subjects responding to fasciotomy, there is a significant reduction in IMCP below that of preoperative groups (P<0.001). Postoperative responders to fasciotomy have no significant differences in IMCP from asymptomatic controls (P=0.182). Conclusion: Fasciotomy reduces IMCP in all patients. Larger studies are required to confirm that the reduction in IMCP accounts for differences in functional outcomes and pain reductions seen in postoperative patients with CECS.